2022
DOI: 10.1108/mf-08-2021-0386
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis on household financial vulnerability in India: exploring the role of financial knowledge, impulsivity and money management skills

Abstract: PurposeThe COVID-19 pandemic has exposed the financial-economic vulnerability of the public and threatened the household financial stability, especially of the low-income group population, in developing economies such as India. The assessment of household financial vulnerability has gained considerable attention these days, especially in poor and developing countries. This article seeks to assess the level of household financial vulnerability in India, based on a household survey conducted across India.Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Studies have found that higher levels of resilience were associated with lower levels of financial fragility one year after the start of the pandemic (Clark and Mitchell, 2022). The women in our study exhibited financial fragility, particularly due to their low levels of financial security (Singh and Malik, 2022). Consequently, their financial resilience was also low.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies have found that higher levels of resilience were associated with lower levels of financial fragility one year after the start of the pandemic (Clark and Mitchell, 2022). The women in our study exhibited financial fragility, particularly due to their low levels of financial security (Singh and Malik, 2022). Consequently, their financial resilience was also low.…”
Section: Resultsmentioning
confidence: 86%
“…Constructing financial knowledge and financial awareness can contribute to reducing financial vulnerability (Singh and Malik, 2022), allowing for prudent money management and a better perception of financial control (Lusardi et al ., 2021; O'Connor et al ., 2019). Moreover, it is important to monitor indicators of anxiety and financial stress, which can have long-term consequences, such as making retirement financial planning difficult (Hasler et al ., 2021) and reducing financial well-being.…”
Section: Discussion Limitations and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, household FV has gained the attention of scholars and policymakers. Some studies have defined FV as a consequence of high levels of household debt (Allgood & Walstad, 2016; Disney & Gathergood, 2011; Ray et al, 2019), while broader definitions encompass households’ inability to meet basic living expenses (Loke, 2016; Singh & Malik, 2022) or unforeseen expenses (Lusardi et al, 2011; Philippas & Avdoulas, 2020), as well as to raise a given amount of funds to tackle a rush (Friedline & West, 2016; Lusardi et al, 2011; Philippas & Avdoulas, 2020; West & Mottola, 2016). Additionally, adverse economic shocks (e.g., interest or unemployment rates, adjustments in housing or retirement accounts…) can also render households financially vulnerable (Ali et al, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…One possible explanation for this inconclusive evidence is the lack of a common definition of FV (Fernández-López, Álvarez-Espiño, Rey-Ares, & Castro-González, 2023; Seldal & Nyhus, 2022; Singh & Malik, 2022). Consequently, researchers have resorted to measuring FV using a single financial behavior or perspective, either objective or subjective.…”
Section: Introductionmentioning
confidence: 99%